Antimicrobial application of nanofibrous mats self-assembled with quaternized chitosan and soy protein isolate. (20th November 2015) - Pan, Yijun; Huang, Xingjian; Shi, Xiaowen; Zhan, Yingfei; Fan, Gang; Pan, Siyi; Tian, Jing; Deng, Hongbing; Du, Yumin
Highlights: HTCC and SPI were alternately deposited on CA mats via LBL self-assembly technique. HTCC/SPI-bilayer-modified CA mats possessed antimicrobial activity. Antimicrobial effects positively correlated with number of bilayers on CA mats. HTCC on the outermost layer of mats enhanced the antimicrobial effects. Abstract: Positively charged N -[(2-hydroxy-3-trimethylammonium) propyl] chitosan chloride (HTCC) and negatively charged soy protein isolate (SPI) were alternately assembled on cellulose acetate (CA) electrospun nanofibrous mats via electrostatic layer-by-layer self-assembly technique. CA nanofibrous mats coated with bilayers of HTCC and SPI possessed more orderly-arranged structure than uncoated CA mats according to the observation from scanning electron microscopy images. The average diameter of the nanofibers was enlarged by the increase of the bilayer number. X-ray photoelectron spectroscopy indicated that HTCC and SPI were coated on the surface of the CA mats successfully. The average diameters of inhibition zones of (HTCC/SPI)10.5 -films-coated nanofibrous mats against Escherichia coli and Staphylococcus aureus were 9.6 mm and 11.53 mm, respectively, which demonstrated the highest antimicrobial activity among samples in presented study.